2011
DOI: 10.3892/mmr.2011.594
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine prevents hepatic fibrosis in a non-alcoholic steatohepatitis model induced by an L-methionine-and choline-deficient diet

Abstract: Abstract. Recent reports have shown that nifedipine, a calcium channel blocker, increases peroxisome proliferator-activated receptor-γ (PPARγ) activity. Since PPARγ agonists, such as pioglitazone and rosiglitazone, are effective in reducing non-alcoholic steatohepatitis (NASH) and cirrhosis in animal models, we examined the protective effects of nifedipine, as compared with bezafibrate, a PPARα agonist, in a NASH model induced by an L-methionine-and choline-deficient (MCD) diet. An MCD diet for 20 weeks change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is known than PPARγ plays a role in the maintenance of a quiescent HSC phenotype, and that PPARγ agonists suppress the fibrogenic potential of HSCs in vitro and in vivo ; specifically, pioglitazone and rosiglitazone, two kinds of PPARγ agonists, have been shown to alleviate liver inflammation and fibrosis in murine NASH models (Polyzos et al, 2010; Nakagami et al, 2012). Furthermore, pioglitazone also decreased liver fibrosis in patients with NASH (Gastaldelli et al, 2010; Ratziu et al, 2010); though another study reported pioglitazone could decrease inflammation in liver, but did not affect liver fibrosis (Belfort et al, 2006).…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…It is known than PPARγ plays a role in the maintenance of a quiescent HSC phenotype, and that PPARγ agonists suppress the fibrogenic potential of HSCs in vitro and in vivo ; specifically, pioglitazone and rosiglitazone, two kinds of PPARγ agonists, have been shown to alleviate liver inflammation and fibrosis in murine NASH models (Polyzos et al, 2010; Nakagami et al, 2012). Furthermore, pioglitazone also decreased liver fibrosis in patients with NASH (Gastaldelli et al, 2010; Ratziu et al, 2010); though another study reported pioglitazone could decrease inflammation in liver, but did not affect liver fibrosis (Belfort et al, 2006).…”
Section: Nuclear Receptorsmentioning
confidence: 99%